The Effect of the Crude Terpenoids Compounds of Melia Azedrach Leaves and Fruits on Some Biological Aspects of Whitefly Bemisia tabaci - Majeed, Osama S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
This study was carried out to determine the effects of crude terpenoid compound extracts of Melia azedarach L. leaves and fruits on some biological aspects of whitefly Bemisia tabaci (Genn.) under laboratory conditions of 25 ± 2°C and relative humidity of 65-70%. The results indicated a significant effect on eggs and immature stages when treated with 0.5, 1, 1.5, and 2 mg/ml of leaves and fruits. The mortality rate increased with concentration. It reached 98.68, 100, 100, 95.70, 86.30, and 42.68% for eggs, 1st, 2nd, and 3rd nymphal instars, pupa, and adults, respectively, at a concentration of 2 mg/ml for leaves extract. At the same time, it reached 94.86, 100,100, 100, 87.89, and 44.90% for eggs, 1st, 2nd, and 3rd nymphal instars, pupa, and adults, respectively, at a concentration of 2 mg/ml for fruit extract. Also, the proportion of adults who emerged from sprayed eggs reduced to 91.53% and 95.72% when treated with 2 mg/ml of leaves and fruit extracts, respectively. While the developmental period increased to 23.50 and 24.00 days at 2 mg/ml when treated with terpenoid extracts of the leaves and fruits, respectively, compared with 21.00 and 20.83 days at control.